THE IMPORTANCE OF EFFICIENT USE OF ENERGY RESOURCES ON DIRECT FOREIGN INVESTMENTS HEADED TOWARDS THE DEVELOPING COUNTRIES (Third Sector Social Economic Review, 2020)
With the globalization process, foreign direct investments have become an important tool in being achieve ddevelopment goals of developing countries. Therefore, it is very important for the developing countries to determine the determinants of foreign direct investments and to be managed the process well.In the literature, although elements such as raw materials, workers' wages and energy costs are generally seen as an important determinant for foreign direct investments, this study draws attention to the effect of efficient use of energy resources on foreign direct investments. Panel regression analysis was implemented by using data from 2000-2014 period (15 years) of seven selected developing countries in Europe and Central Asia. As a result of the analysis, it has been seen that reducing  the energy density, which is an indicator of the efficient use of energy resources, is an important determinant in the context of attracting foreign direct investment.
Keywords: Developing Countries; Foreign Direct Investment; Energy Efficiency; Energy Density